Recent cockroach bacterial contamination trend in the human dwelling environments: A systematic review and meta-analysis - Nasirian, Hassan (Bangladesh Journal of Medical Science, 2019)
Background: Cockroaches have been compromised with the human environment posing some risks to humans. Objective: A systematic review and meta-analysis study about the bacterial contamination of cockroaches in the human dwelling environmentswere investigated. Methodology: Relevant topics about bacterial contamination of cockroaches were collected from scientific websites between January 2016 and January 2017. After a preliminary review 32 of the collected topics were selected to become part of the detailed synthesis meta-analysis review. Results: Results showed that the global mean bacterial contamination trend of cockroaches and Periplaneta americana ranged 45.0-80.0 and 55.0-75.0 %, respectively which were increased while it were 90.0-50.0 % for Blattella germanica which decreased in recent years. The global mean bacterial contamination of cockroaches, P. americana and B. germanica was also 67.9, 72.9 and 62.9 %, respectively which P. Americana had the most global mean bacterial contamination. Statistical analysis didn’t show any significant differences between any combination of bacterial contamination of the cockroaches, and P. americana and B. germanica surfaces such as totalexternal, total-internal and external-internal; any type environment of cockroaches, P. americana and B. germanica including households, hospitals and miscellaneous; any combination of bacterial contamination such as between total-total, external-external and internal-internal surfaces of the P. americana and B. germanica; and P. americana and B. germanica in combination environments of households-households, hospitals-hospitals and miscellaneous-miscellaneous (P > 0.05). Conclusions: The external and internal surfaces of any type cockroach have equal importance ofbacterial contamination and they threaten human health in the any type environment. Bangladesh Journal of Medical Science Vol.18(3) 2019 p.540-545